The influence of digital culture, coordination and job satisfaction on employee performance with organizational commitment as a mediation variable - Pakpahan, Onny; Liswandi, Liswandi; Sudarmo, Agnes Puspitasari (International Journal on Social Science, Economics and Art, 2024)
Government organizations must always improve their performance according to the needs of a developing society. The survey results showed that the public did not get satisfaction so they got the highest "B" score for public services and service units. The basis for implementing Community Satisfaction Monitoring is the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Monitoring in Public Service Units. This research aims to test and analyze the influence of digital culture, coordination, job satisfaction on the performance of financial manager employees of KPPN Balige work partners through the mediating variable, namely organizational commitment, using data processing techniques for a sample of 92 employees. Data collection was carried out by distributing questionnaires that used a 5-point Likert Scale to measure the statements of the five variables studied. The analysis technique used is multiple linear regression analysis. The research results show that partially coordination, job satisfaction, organizational commitment and employee performance do not have a significant effect on the performance of financial manager employees. Only the digital culture variable influences the performance of financial management employees of KPPN Balige partners who oversee 4 (four) districts. So it can be concluded that in general digital culture, coordination and job satisfaction have no or very little influence on organizational commitment because most employees do not want to work in the current agency or organization.